2015
DOI: 10.1074/jbc.m114.621581
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type Human γD-crystallin Promotes Aggregation of Its Oxidation-mimicking, Misfolding-prone W42Q Mutant

Abstract: Background: Oxidative damage and destabilizing mutations in ␥-crystallins lead to cataract disease. Results: Addition of wild-type ␥D-crystallin promotes aggregation of the oxidation-mimicking W42Q mutant, yet the wild-type protein escapes coaggregation. Conclusion: Wild-type human ␥D-crystallin can serve as a catalyst for aggregation of its misfolding-prone point mutant.Significance: This finding provides a model of pathology caused by wild-type/mutant or undamaged/damaged protein interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(89 citation statements)
references
References 61 publications
10
78
1
Order By: Relevance
“…DSC ( Figure 1C) revealed that there was almost no difference in the temperature of the two mutants' unfolding transitions. The available chemical denaturation curves confirm similar stability of W42Q and W42R (39,51). Table 1 summarizes melting temperatures obtained from DSC of the WT and several mutant constructs.…”
Section: W42r and W42q Are Similar To Each Other In Stability And Aggmentioning
confidence: 85%
See 3 more Smart Citations
“…DSC ( Figure 1C) revealed that there was almost no difference in the temperature of the two mutants' unfolding transitions. The available chemical denaturation curves confirm similar stability of W42Q and W42R (39,51). Table 1 summarizes melting temperatures obtained from DSC of the WT and several mutant constructs.…”
Section: W42r and W42q Are Similar To Each Other In Stability And Aggmentioning
confidence: 85%
“…We have previously reported that the aggregates formed by the temperature-sensitive Trp mutants of γD-crystallin under near-physiological conditions are neither disulfide-bridged nor amyloid and expose few hydrophobic residues (39,50). These observations raised the question of whether a seeding effect exists in this aggregation pathway.…”
Section: W42r and W42q Aggregation Occurs At Solution Redox Potentialmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, high levels of oxidation of αB-crystallin Met-68 have been reported in cataractous lenses (Yanshole et al 2013). The oxidation-mimicking W42Q mutant of γD-crystallin readily shows reduced thermal stability and aggregates in the presence of WT γD-crystallin (Serebryany and King 2015). Likewise, the presence of oxidised βA3-crystallin peptide (152-166) increases aggregation in both α-and γ-crystallin bovine lens fractions (Udupa and Sharma 2005).…”
Section: Oxidationmentioning
confidence: 99%